Will the real phylogeneticists please stand up? - Wiley, Edward O.; Chakrabarty, Prosanta; Craig, Matthew T.; Davis, Matthew P.; Holcroft, Nancy I.; Mayden, Richard L.; Smith, Wm. Leo (Zootaxa, 2011)
In a recently published commentary, Mooi & Gill asserted that there is a crisis brewing in systematic ichthyology caused by a failure of investigators to apply the basic tenets of outgroup comparison to recover clades based solely on shared apomorphic characters. The result, they claim, is that many recent analyses disregard real synapomorphies and discover clades by phenetic rather than phylogenetic principles. We take the opportunity to refute this claim and assert that matrix-based analyses, whether parametric or nonparametric, satisfy the basic tenets of Hennig’s methods, resulting in monophyletic groups confirmed by synapomorphies.